Upright versus lying down position in second stage of labour in nulliparous women with low dose epidural: BUMPES randomised controlled trial - Bick, D; Briley, A; Brocklehurst, P; Hardy, P; Juszczak, E; Lynch, L; MacArthur, C; Moore, P; Nolan, M; Rivero-Arias, O; Sanders, J; Shennan, A; et al. (BMJ Publishing Group, 2017)
Objective To determine whether being upright in the second stage of labour in nulliparous women with a low dose epidural increases the chance of spontaneous vaginal birth compared with lying down. Design Multicentre pragmatic individually randomised controlled trial. Setting 41 UK hospital labour wards. Participants 3093 nulliparous women aged 16 or older, at term with a singleton cephalic presentation and in the second stage of labour with epidural analgesia. Interventions Women were allocated to an upright or lying down position, using a secure web based randomisation service, stratified by centre, with no masking of participants or clinicians to the trial interventions. Main Outcome Measures The primary outcome was spontaneous vaginal birth. Women were analysed in the groups into which they were randomly allocated, regardless of position recorded at any time during the second stage of labour (excluding women with no valid consent, who withdrew, or who did not reach second stage before delivery). Secondary outcomes included mode of birth, perineal trauma, infant Apgar score <4 at five minutes, admission to a neonatal unit, and longer term included maternal physical and psychological health, incontinence, and infant gross developmental delay. Results Between 4 October 2010 and 31 January 2014, 3236 women were randomised and 3093 (95.6%) included in the primary analysis (1556 in the upright group and 1537 in the lying down group). Significantly fewer spontaneous vaginal births occurred in women in the upright group: 35.2% (548/1556) compared with 41.1% (632/1537) in the lying down group (adjusted risk ratio 0.86, 95% confidence interval 0.78 to 0.94). This represents a 5.9% absolute increase in the chance of spontaneous vaginal birth in the lying down group (number needed to treat 17, 95% confidence interval 11 to 40). No evidence of differences was found for most of the secondary maternal, neonatal, or longer term outcomes including instrumental vaginal delivery (adjusted risk ratio 1.08, 99% confidence interval 0.99 to 1.18), obstetric anal sphincter injury (1.27, 0.88 to 1.84), infant Apgar score <4 at five minutes (0.66, 0.06 to 6.88), and maternal faecal incontinence at one year (1.18, 0.61 to 2.28). Conclusions Evidence shows that lying down in the second stage of labour results in more spontaneous vaginal births in nulliparous women with epidural analgesia, with no apparent disadvantages in relation to short or longer term outcomes for mother or baby.